Kindling the flame of integrin activation and function with kindlins - Plow, Edward F. (2009)
PURPOSE OF REVIEW: There are three kindlin family members in vertebrates, which have high-sequence homology and a common organization signature with a C-terminal 4.1, ezrin, radixin, moesin (FERM) domain bisected by a pleckstrin-homology domain. Although the cell and tissue distributions of the three kindlins differ, there is a consistent and close interrelationship between kindlins and integrins, and alterations of kindlin expression affect integrin-dependent functions. However, in-vivo data on the functions of the kindlins and their mechanisms of action have been lacking. RECENT FINDINGS: Recent studies have shown that deficiencies of each of the three kindlins result in profound and distinct phenotypes, ranging from skin and intestinal defects (kindlin-1), embryonic lethality due to cardiac developmental problems (kindlin-2), to marked abnormalities in platelet, leukocyte and erythrocyte function (kindlin-3). A human disease characterized by bleeding, frequent infections and osteopetrosis has now been attributed to mutations in the gene encoding for kindlin-3. These defects are consistent with recent data showing that kindlins control integrin activation and function. SUMMARY: The three members of the kindlin family have now been implicated as essential regulators of integrin function in individual cells and in whole organisms.